从鬼话看中国民间文化 = Chinese folk culture from the perspectives of ghost stories - 黄薇颖 Ng, Wei Ying (2013)
中国鬼话在文学领域中常被人们误以为是毫无意义的文学作品。事实上，鬼话 所包含的文学价值不仅次于任何文学作品。随着历史的演变与发展，鬼话并没有为 此而没落。相反，人们对鬼话一直存有浓厚的兴趣。至今，不论是书籍、电视节目 或电影都常会以鬼话为题材。这证明了鬼话在人们的心中有着重要的地位。 由于鬼话出自于民间，因此内容通常会以人们的生活写照为基础。不管是时代 背景、文化习俗或宗教信仰都是鬼话考量的对象。除此之外，因为是民间的产物， 鬼话多数以口耳相传的方式遗留下来。尽管为此，有很多鬼话的出处无从考证，但 是鬼话还是存有一定的教育意义。本文会选出几篇鬼话为例，从中进行简单的分类。 随后将更进一步探讨鬼话的发展与文化意义。The value of Chinese ghost stories as a literary form has long been overshadowed by mainstream literature such as classical poetry, prose, and drama. However, given the fact that ghost stories from the past have been passed down through the generations and still exist, there is no doubt that it is one of the most valuable folk literatures in the present society. Ghost stories continue to be a popular theme in novels, television shows and movies, proving that people still have a keen interest in these tales. Ghost stories are often a mirror image of the peoples’ lives, a representation of the origins of the folktales. As such, ghost stories abound with traditional Chinese culture and customs, including religious influences. Buddhism is one of the largest religions in China; therefore it is common to see the stories laden with Buddhist teachings. This paper seeks to first categorise a selection of ghost stories before going in-depth to discuss the historical development and cultural implications of ghost stories.